SOLPS-ITER modeling of divertor detachment in MAST-U’s super-X double null configuration and comparison to experiment - R. Maurizio; A.W. Leonard; J.H. Yu; J. Harrison; K. Verhaegh; N. Lonigro; A.G. McLean (Nuclear Materials and Energy)
The MAST-U tokamak has recently undergone upgrades to investigate any detachment advantages of the “Super-X Double-Null” magnetic configuration, a concept featuring up-down symmetry with two magnetic nulls and elongated divertor legs with strong wall baffling. This study presents SOLPS-ITER simulations of MAST-U Super-X Double Null discharges, in H-mode conditions, compared to initial 2D imaging measurements of divertor detachment characteristics. In the simulations, the Super-X divertor targets achieve detachment at a substantially lower upstream separatrix density compared to a shorter leg, conventional configuration (CD). As the density increases further in the Super-X configuration, the cold detached front moves upstream towards the X-point. Its speed in the poloidal plane, calculated as the change in front location divided by the corresponding increase in upstream plasma density, decreases by a factor of ∼ 3–4 as the front transitions from the baffled divertor chamber to the main plasma chamber, reaching a speed comparable to that observed in the CD configuration. In a chosen experimental Super-X density ramp discharge, the ionization front, identified using D2 Fulcher emission as a proxy, is already displaced from the target at the start of the divertor fueling ramp, whereas modeling of the same initial phase shows the ionization front still close to the target. As divertor fueling increases, both experiment and modeling show the ionization front moving further upstream towards the divertor throat. However, the associated variation in upstream density is ∼ 2 times larger in the modeling compared to the experiment, resulting in a broader detachment window. Comprehensive modeling efforts are underway to address these discrepancies, with several inaccurate modeling assumptions identified as potential causes of the deviation.